A FeCl(3)-promoted highly atropodiastereoselective cascade reaction: synthetic utility of radical cations in indolostilbene construction - Ahmad, Kartini; Thomas, Noel Francis; Mukhtar, Mat Ropi; Noorbatcha, Ibrahim Ali; Weber, Jean-Frederic Faizal; Nafiah, Mohd Azlan; Velu, Saraswati S; Takeya, Koichi; Morita, Hiroshi; Lim, Chuan-Gee; A Hadi, A Hamid; Awang, Khalijah (Elsevier BV, 2009)
The FeCl(3)-promoted oxidative cyclization/coupling of acetamidostilbenes possessing 3-methoxy, 4-methoxy and 3,5-methoxy substitutions (21), (22) and (23) is described. Only 3,5-substitution gave rise to novel indolostilbenes, each possessing two stereogenic axes (axially chiral but racemic dimers (39) and (40)). The 4-methoxy substituted acetamidostilbenes, by contrast, yielded the bisindoline dimer (36).